BENTUK DAN STRUKTUR SUPERSTISI KATEGORI KEMATIAN DAN ADAT PEMAKAMAN PADA MASYARAKAT MELAYU RUMBAI TIMUR - Robiatul Husna Siregar; Erni (Literasi: Jurnal Ilmiah Pendidikan Bahasa, Sastra Indonesia dan Daerah, 2023)
Superstition is a belief that cannot be proven logically and does not necessarily occur. In this study the authors took one village among the villages in East Rumbai District, namely the village of Tebing Tinggi Okura. This research is also motivated by the researcher's desire to find out the structure and meaning contained in the superstitious East Rumbai Malay community which is formed by the relationship between different life values ​​and beliefs. The purpose of this study is to describe the form and structure of the superstitious categories of death and burial customs in the Malay community in Tebing Tinggi Okura Rumbai Timur Village, Pekanbaru City. The approach to this study uses a qualitative approach while the research method is a qualitative descriptive method with a type of field research. The analysis in this study was carried out in three stages, namely data reduction, data presentation and conclusion. Based on the results of the analysis in this study, there were 27 superstitious forms of death category data and funeral customs. Of the 27 data that has been obtained, 23 data are classified into a two-part structure, namely cause and effect, while the other 4 data include a three-part structure, namely a sign, a change from one state to another (conversion), and a result. The East Rumbai Malay community, especially the village of Tebing Tinggi Okura, has instilled superstitious values ​​in their daily lives, because the use of this superstition can regulate the order of norms in their collective society, especially in death and funeral customs in the East Rumbai Malay community.